Liberalization and Indias Business Cycle Synchronization with the US - Biru Paksha Paul (Indian Economic Review, 2010)
In the wake of Indias liberalization since the early 1990s, the countrys monetary and trade integration with the leading economy, the US, has increased more than ever before. While literature on whether financial integration leads to greater business cycle synchronization is ambiguous, this study finds that Indias business cycle has increasingly been synchronized with the US counterpart as liberalization has intensified over time. Since US output fluctuations are arguably exogenous to India, this synchronization, as estimated in impulse responses, variance decompositions, correlations, and GARCH models, can be viewed as business cycle transmission from the US to India. The pattern of movements in monetary, trade, and output variables based on gradually improving openness suggests that Indias augmenting business cycle synchronization with the US is mainly attributable to the channels of trade and monetary policy.